The Moderating Effect of Dividend Policy on Corporate Image of Corporate Social Responsibility on Financial Performance - Sonia Mareta; - Lismawati; Eddy Suranta; Fenny Marietza; - Fadli (Universitas Trunojoyo Madura, 2023)
This research aim to investigate of the moderating effect of dividend policy on company image resulting from Corporate Social Responsibility (CSR) activities on the firm’s financial performance relathionship. This research employ quantitative method by applying it empirically to examine the financial performance of companies that are consistently on the LQ-45 of the Indonesian Stock Exchange on year 2020-2022. The model conducted in this research produces accurate estimation of the firm’s financial performance over several periods. The result found the importance of company dividend policy in moderating the influence of corporate image generated by Corporate Social Responsibility on company financial performance. The result also found that the company's financial performance results have a better for corporate image of corporate social responsibility and dividend policy. Therefore, this reseach can help stakeholders to identify investment decisions as they search for the most valuable companies and groups of companies to invest in. Additionally, our findings can help policymakers to identify trends in corporate financial performance over time.